a MODEL SINERGI PEMBANGUNAN DESA: INTEGRASI INFRASTRUKTUR, PEMBERDAYAAN, DAN PEMBINAAN UNTUK KEBERLANJUTAN - Riyoldi, Riyoldi; Nge, Herri Junius; Apriyani, Eka; Rudiyanto, Yustinus; Nazari, Nada Azwa; Padilah, Ahirul Habib (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
This study aims to formulate a synergistic village development model that integrates three key elements infrastructure development, community empowerment, and governance capacity-building as a comprehensive approach to achieving sustainable village development. Academically, this study is significant because it offers an integrative perspective on village development, which has often been approached in a fragmented or sectoral manner. Practically, the research provides relevant guidance for village governments and development stakeholders in designing more effective development strategies. The study employs a qualitative approach through a literature review by examining policy documents, previous research findings, and academic literature related to village development and community capacity strengthening. The findings indicate that the success of village development is largely determined by the interconnection among the three elements: infrastructure must support the enhancement of local capacities; empowerment initiatives should strengthen economic and social independence; and governance capacity-building is needed to ensure transparency, accountability, and alignment with local cultural values. This research contributes to filling gaps in the existing literature by proposing an integrative development model that is more holistic and participatory. Practically, the model can serve as a strategic reference for village governments in formulating sustainable development policies.